Costs and benefits of food sharing in Milan - Sadovska, Vera; Voytenko Palgan, Yuliya; Plepys, Andrius; Mont, Oksana (International Institute for Industrial Environmental Economics, Lund University, 2025)
This report presents findings from the case study on food sharing in the city of Milan, Italy, which was performed as part of the project CULTIVATE: Co-designing Food Sharing Innovation for Resilience: https://cultivate-project.eu/ in June 2024 - November 2024. The study aims to understand the economic, social, and environmental aspects of FSIs, which include growing and composting together, cooking and eating together, and redistributing surplus food. The research employs a Mobile Research Lab (MRL) approach, combining desktop research, online interviews, field research, and data analysis. Milan’s food sharing ecosystem stands out as a dynamic and evolving landscape shaped by strong municipal leadership, a robust policy framework, cross-sector collaboration, commitment to systemic change and a deeply rooted culture of civic engagement. Since the launch of the Milan Urban Food Policy Pact in 2015, the city has positioned itself as a global reference point for urban food governance, embedding food sharing into broader strategies for sustainability, social inclusion, and urban resilience. The city’s experience offers valuable insights for other urban areas seeking to build resilient and equitable food systems.
Keywords: Food sharing; urban food system; sharing economy; CULTIVATE